Diabetes, periodontal disease, and novel therapeutic approaches- host modulation therapy - Gu, Ying; Golub, Lorne M.; Lee, Hsi-Ming; Walker, Stephen G. (Frontiers in Clinical Diabetes and Healthcare, 2025)
Diabetes mellitus is a much-studied disorder, characterized by hyperglycemia and numerous oral and medical complications. The latter includes (above all) decreased life-span — and these are widely discussed in the dental and medical literature. The oral complications include impaired wound healing; increased severity of periodontal disease and peri-implantitis; dry mouth (xerostomia); and dental caries. The relationship between diabetes and oral health is bi-directional: Optimal management of local oral disease can profoundly affect the systemic metabolic control of the diabetic patient, and strict management of the patient’s hyperglycemia can reduce its impact on oral disease. The only host modulation therapy (HMT), approved by the U.S. Food and Drug Administration (FDA) to treat periodontal disease, is a novel NON-antimicrobial (low-dose) formulation of doxycycline (Periostat®; 20 mg b.i.d). A publication in Scientific Reports (2017), which supported the clinical rationale of efficacy and safety of low-dose doxycycline in diabetics, stated: “doxycycline not only ameliorated insulin resistance, fasting blood glucose, and insulin levels, and lipid profiles in the circulation and liver, but also improved islet morphology and increased glucose-stimulated insulin secretion.” Additional developments include the biphenolic chemically-modified curcumins, as HMT for managing oral diseases. A lead compound, chemically-modified curcumin 2.24 (CMC2.24), has demonstrated safety and efficacy in vitro, in cell culture, and in vivo using mouse, rat, rabbit, and dog models of disease. In conclusion, novel host-modulation compounds have shown significant promise as adjuncts to traditional local therapy in the clinical management of periodontal and other oral diseases.